2016
DOI: 10.1016/j.jpeds.2016.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Nonsteroidal Anti-Inflammatory Drug without Antibiotics for Acute Viral Infection Increases the Empyema Risk in Children: A Matched Case-Control Study

Abstract: NSAIDs use during acute viral infection is associated with an increased risk of empyema in children, and antibiotics are associated with a decreased risk. The presence of antibiotic-NSAIDs interaction with this risk is suggested. These findings suggest that NSAIDs should not be recommended as a first-line antipyretic treatment during acute viral infections in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 39 publications
(46 reference statements)
3
75
0
4
Order By: Relevance
“…There is increasing evidence that ibuprofen in case of respiratory infections or pneumonia may facilitate empyema and complicated pneumonia in children [132135] and adults [136], possibly via modification of neutrophil and alveolar macrophages functionality (chemotaxis, adhesion, aggregation, and degranulation [137]) and the inhibition of prostaglandin synthesis as well as via cover-up effects on subjective symptoms, thereby delaying diagnosis and treatment. This may explain the correlation between increased sales of ibuprofen for children and complicated pneumonia in France [133], although reverse causation is also possible.…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that ibuprofen in case of respiratory infections or pneumonia may facilitate empyema and complicated pneumonia in children [132135] and adults [136], possibly via modification of neutrophil and alveolar macrophages functionality (chemotaxis, adhesion, aggregation, and degranulation [137]) and the inhibition of prostaglandin synthesis as well as via cover-up effects on subjective symptoms, thereby delaying diagnosis and treatment. This may explain the correlation between increased sales of ibuprofen for children and complicated pneumonia in France [133], although reverse causation is also possible.…”
Section: Discussionmentioning
confidence: 99%
“…This included 269 from MEDLINE, 1214 from EMBASE, and 25 studies from COCHRANE CENTRAL database, and 4 studies from searching reference lists. Twelve potential publications that met the inclusion criteria after title and abstract review were identified 3–12, 19, 20 . After full text review, two additional studies with no active comparator (case series) were excluded (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…There were five nested case‐control studies, 4, 5, 7, 8, 12 three cohort studies, 3, 6, 11 and two population‐based case‐control studies 9, 10 (Table ). In total, the studies included 59,724 adults across 5 of the studies (range = 57–59,250) 3, 6, 7, 11, 12 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Möglicherweise ist das auch der Tatsache zu verdanken, dass die Kinder in der Klinik fiebern dürfen, sofern sie nicht darunter leiden. Es gibt eine zunehmende Anzahl an Berichten von Verschleppung und Komplikationen von Lungenentzündungen im Zusammenhang mit Ibuprofen-Gaben [27][28][29][30], mit paralleler Entwicklung zwischen Pleuraempyem Inzidenz und dem Verkauf von Ibuprofen-Saft für Kinder in Frankreich [31]. In einer taiwanesischen Studie wurden Risikofaktoren für die Progression zu Erguss, Empyem oder nekrotisierender Pneumonie untersucht: Alter < 2 Jahre, Pleuraerguss als Aufnahmediagnose, Hb < 10 g / dl, Leukozyten-Zahl > 17.500/ml, Tachypnoe und Dauer bis zur Entfieberung > 3 Tage [32].…”
Section: Verlaufunclassified